2022
DOI: 10.1684/epd.2021.1406
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy in neurodegenerative diseases

Abstract: Although epilepsy as a comorbidity in neurodegenerative disorders is increasingly recognized, its incidence is still underestimated and the features of epilepsy in the different neurodegenerative conditions are still poorly defined. Improved health care, resulting in increased longevity, will unavoidably lead to an increment of epilepsy cases in the elderly. Thus, it is conceivable to expect that neurologists will have to deal with these comorbid conditions to a growing extent in the future. In this seminar, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 96 publications
(186 reference statements)
0
18
0
Order By: Relevance
“…Specifically, the incidence of hippocampus-related degenerative diseases, such as AD and temporal lobe epilepsy (TLE), is increasing, partly because the hippocampus is susceptible to toxic substances such as excitatory amino acids, resulting in neuronal dysfunction, cognitive impairment, and death (3). Late-onset epilepsy is mostly secondary to brain diseases such as stroke, tumor, and neurodegenerative diseases, and many of them are of unknown etiology (4). In patients older than 65 years, neurodegenerative conditions accounted for ∼10% of all late-onset epilepsy cases, most of which are AD (5).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the incidence of hippocampus-related degenerative diseases, such as AD and temporal lobe epilepsy (TLE), is increasing, partly because the hippocampus is susceptible to toxic substances such as excitatory amino acids, resulting in neuronal dysfunction, cognitive impairment, and death (3). Late-onset epilepsy is mostly secondary to brain diseases such as stroke, tumor, and neurodegenerative diseases, and many of them are of unknown etiology (4). In patients older than 65 years, neurodegenerative conditions accounted for ∼10% of all late-onset epilepsy cases, most of which are AD (5).…”
Section: Introductionmentioning
confidence: 99%
“…The GO biological process and KEGG pathway enrichment analyses, performed by the ShinyGO ( , accessed on 15 February 2022, version 0.77) tool, showed that most proteins significantly enriched in established biological processes were involved in the electron transport chain, cellular respiration, cellular respiration, microtubule cytoskeleton organization and protein-containing complex assembly ( Figure 3 B). The KEGG enrichment analysis revealed the identified hub genes as associated with key neurodegenerative (e.g., Huntington’s, Parkinson’s and Alzheimer’s) diseases often comorbid with epilepsy [ 12 , 13 ]. Interestingly, significant over-enrichment was seen here for the gap junction pathway and temperature regulation ( Figure 3 A).…”
Section: Discussion Of Identified Pathwaysmentioning
confidence: 99%
“…Epilepsy occurs when an abnormal discharge of neurons in the brain leads to transient dysfunction of the CNS. 257 The presence of epilepsy in neurodegenerative diseases is increasingly recognized, 258 and its incidence is still underestimated. In recent years, several studies have established the relationship among exosomes, miRNAs, and epilepsy.…”
Section: Epilepsymentioning
confidence: 99%